Description of a stunning new species of Phlegra Simon, 1876 from southern Spain and redescription of an enigmatic Phlegra species from northern Africa (Araneae: Salticidae) - Azarkina, Galina N.; Pérez-Gómez, Álvaro; Sánchez-García, Iñigo (Zootaxa, 2022)
A new species of jumping spider, Phlegra blaugrana sp. nov., is described (♂♀, Cádiz Province, Spain). Phlegra nitidiventris Lucas, 1846 is redescribed, and the female is described for the first time. Phlegra sapphirina Thorell, 1875 syn. nov. is synonymized with P. nitidiventris. A distribution map for P. blaugrana sp. nov. and P. nitidiventris is provided, and elements of the courtship behaviour of P. blaugrana sp. nov. are described.